Liver transaminase levels during pregnancy: a Japanese multicenter study - Ushida, Takafumi; Kotani, Tomomi; Kinoshita, Fumie; Imai, Kenji; Nakano-Kobayashi, Tomoko; Nakamura, Noriyuki; Moriyama, Yoshinori; Yoshida, Shigeru; Yamashita, Mamoru; Kajiyama, Hiroaki (The journal of maternal-fetal & neonatal medicine, 2022)
There are conflicting reports on the effect of pregnancy on liver transaminase (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]) levels. In this study, we sought to investigate the trajectories of AST and ALT levels during normal pregnancy and to compare them with AST and ALT levels of matched nonpregnant controls. Our multicenter retrospective study included 34,396 women who delivered at term at 12 primary maternity care units between January 2011 and December 2018 and 57,152 nonpregnant women younger than 45 years who received a medical checkup between 2016 and 2019. After matching at a ratio of 1:1 for adjustment of several factors (age, weight, and height), a total of 30,460 normal pregnant women and 30,460 nonpregnant women were selected for this study. We measured serum AST and ALT levels during each trimester and the postpartum period to compare with those of the nonpregnant women. The ALT level began to decrease in the first half of the third trimester and was lowest in the second half of third trimester and at postpartum day 1 (median [interquartile range]: 8 [6-11] U/L, 8 [6-10] U/L, respectively). The decline reversed and returned to the level of a nonpregnant state by postpartum days 2-7. The AST level remained unchanged regardless of pregnancy. The prevalence of abnormal liver transaminases (AST >40 U/L and ALT >40 U/L) was <1% at third trimester; however, it increased to 3-5% on postpartum days 2-7. The ALT level was lower during pregnancy compared with nonpregnant women matched for several factors, whereas the AST level remained unchanged during pregnancy. Understanding the trajectories of AST and ALT levels during pregnancy may facilitate early recognition and diagnosis of impaired liver function, including liver disease and pregnancy complications that affect liver transaminases, such as pre-eclampsia and HELLP (hemolysis, elevated liver enzymes, and low platelet count) syndrome.